2021
DOI: 10.25259/sni_223_2021
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment options and prognostic factors for ruptured distal anterior cerebral artery aneurysms

Abstract: Background: Distal anterior cerebral artery (ACA) aneurysms are rare, representing 1–9% of all intracranial aneurysms. The best treatment strategy for these aneurysms continues to be debated. We clarified the clinical features and treatment outcomes of patients with ruptured distal ACA aneurysms according to the treatment options at our institute. Methods: Thirty-seven consecutive patients (26 women; mean age, 65.2 years) with ruptured distal ACA aneurysms who underwent surgical clipping or coil embolizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition, Martin Lehecka et al ( 4 ) reported that advanced age and higher Hunt-Hess classification (III-V) were risk factors for poor prognosis in ruptured DACAA. Yushiro Take’s study of 37 surgically treated DACAA cases also indicated that WFNs grade (IV-V) and intracranial hematoma were risk factors for poor prognosis ( 20 ). In light of these findings, we conducted univariate and multivariate Cox regression analyses on 17 factors that could potentially affect the survival status of patients with ruptured DACAA at the 2-year mark after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Martin Lehecka et al ( 4 ) reported that advanced age and higher Hunt-Hess classification (III-V) were risk factors for poor prognosis in ruptured DACAA. Yushiro Take’s study of 37 surgically treated DACAA cases also indicated that WFNs grade (IV-V) and intracranial hematoma were risk factors for poor prognosis ( 20 ). In light of these findings, we conducted univariate and multivariate Cox regression analyses on 17 factors that could potentially affect the survival status of patients with ruptured DACAA at the 2-year mark after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]9] Previous studies have reported that ruptured DACA aneurysms are more frequently complicated with intracerebral hematomas than aneurysms in other portions, although the rates vary from 17% to 73%. [1,3,13] Saccular aneurysms located in the distal portion of the genu are more frequently associated with ACA anomalies, such as bihemispheric type ACA or accessory ACA, which are considered to be primarily caused by hemodynamic stress. [3,6,8,9] As cerebral aneurysms may occur in the same portion following head trauma, it is necessary to confirm any history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, almost all aneurysms in the supracallosal portion were treated with aneurysmal neck clipping. [ 1 , 13 ] Compared with aneurysms in the genu portion, clipping surgery has a shallower operative field and is less likely to cause disorientation. Pericallosal artery aneurysms also tend to be wide-neck aneurysms that involve cortical branches from the dome neck despite their relatively small size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations